Evaluation of Adenovirus-36 (Ad-36) antibody seropositivity and adipokine levels in obese children. (July 2017) - Kocazeybek, Bekir; Dinc, Harika Oyku; Ergin, Sevgi; Saribas, Suat; Ozcabi, Bahar Taskın; Cizmecigil, Utku; Altan, Eda; Atalik, Kevser; Yüksel, Pelin; Taner, Zeynep; Karakullukcu, Asiye; Sirekbasan, Serhat; et al.
Abstract: Adenovirus 36 (Ad-36) has recently been suggested as a possible contributor to the current obesity epidemic. The aim of this study was to investigate the prevalence of Ad-36 antibodies in obese children, as well as investigate the role of serum leptin and lipid levels in Ad-36-obesity. Seventy-one obese children and 62 non-obese children were included as the patient group (PG), including the healthy control group (HCG), respectively. Simultaneously, Ad-36 antibodies and adipokine levels were assessed with serum neutralization assays (SNA) and ELISA. Ad-36 antibody was detected in 9 patients (12.7%) and 1 patient (1.6%) in both the PG and HCG, respectively, while a significant difference was detected between groups ( p  < 0.05). Although serum LDL, total cholesterol, triglycerides and leptin levels were detected significantly higher, adiponectin level was detected paradoxically lower in the PG. However, a significant difference was not detected for lipids and leptin levels; adiponectin levels were found to be significantly lower in Ad-36 antibody-positive PG ( p  < 0.05). In conclusion, we suggest there is an association between Ad-36 and obesity in children, including IL-6 levels increasing in obese children with Ad-36 seropositivity. Conversely, adiponectin levels in obese children with Ad-36 seropositivity were higher. As such, there is a need for studies to understand the mechanisms underlying this observation.